Freeze-thaw and wetting-drying effects on the hydromechanical behavior of a stabilized expansive soil. (15th March 2021) - Ding, Lu-qiang; Vanapalli, Sai K.; Zou, Wei-lie; Han, Zhong; Wang, Xie-qun
Highlights: Cementation and FT cycles reduce soils' water retention capacity. Moisture sensitivity of M R, q u, E 1%, S u1% reduce upon cementation and FT cycles. Proposed equations to predict the M R for cementation and FT influenced soils. Abstract: This study evaluates the effects of post-compaction wetting–drying (WD) process, freeze–thaw (FT) cycles and cement content (CC) on the microstructure, volumetric strain ( ε v ), soil–water characteristic curve (SWCC), resilient modulus ( M R ), unconfined compressive strength ( q u ), and reloading modulus ( E 1% ) and axial stress ( S u1% ) at 1% strain level of a cement-stabilized expansive soil. The specimens compacted with different CC (i.e. 0%, 2%, 4% and 6%) were subjected to different number of FT cycles (i.e. NFT = 0, 1, 3 and 10). They were then dried or wetted to different moisture contents before the determination of the (i) SWCC using filter paper method, (ii) M R from cyclic triaxial tests, and (iii) q u, E 1%, and S u1% from unconfined compression tests. The microstructural changes in the test specimens were determined using mercury intrusion porosimetry and scanning electron microscope tests. Experimental results reveal that cement stabilization and cracks induced during FT cycles cause a significant reduction in the specimen's water retention capacity and the scale of volumetric strain upon moisture content fluctuation. The M R, q u, E 1% and S u1% typically decrease with NFT but increase with CC. However, their variation with moisture content changes is less significant after stabilization or FT cycles. Performance of several empirical models for predicting the M R, q u, E 1% or S u1% was examined. Similar trends in behavior were found for M R - q u, M R - E 1% and M R - S u1% relationships for the specimens tested with different CC, NFT and water content. A simple hyperbolic model proposed in this study for predicting these relationships is validated. The studies presented in this paper are helpful for the design and analysis of stabilized expansive soils used as pavement subgrade considering the influence of complex environmental factors.